Analisis Penerapan Etika Jual Beli Islami Dalam Meminimalisir Distorsi Pasar Pada Pasar Tradisional (Studi Kasus Pada Pasar Induk Giwangan Yogyakarta) - Meichio Lesmana; Siti Nurma Rosmita; Andika Rendra Bimantara (University of Darussalam Gontor, 2020)
In Islamic economics, the market is creat to achieve market equilibrium. But the reality in the field is still challenging to find a market where the mechanism is imbalanced, which is not compatible with the ideal market according to Islamic principles. Many internal and external factors influence the disruption of the market mechanism. The disturbances that occur are known as market distortions. The existence of irregularities in the market is inevitable, where this behavior is far from the ethics of trade in Islam. The purpose of this study was to determine whether the traders in the Giwangan traditional market, which is dominated by Muslim traders, have implemented Islamic trading ethics to minimize market distortions. This research uses qualitative research with a field study approach and uses observation and interview methods. Based on the research results, it can be concluded that there is an Islamic trading ethic that has been practiced by traders in the Giwangan market, namely; honesty in transactions both in terms of quality and scale, the halalness of the products sold, a friendly and generous attitude, and the absence of unfair competition. But from that, there is such an unpracticed trade ethic as a lack of justice to new consumers and customers and a false oath of exaggeration in the quality of the goods sold. Therefore, it could be said that the Giwangan traditional market has attempted to trade by Islamic Sharia, although it has not been fully implemented.